Human Resource Management, Global Edition - Dessler, Gary (Pearson International Content, 2023)
Human Resource Management introduces you to the daily tools and skills you’ll need to function as successful managers, in both HR and business in general. Using a practical approach, the text explores the evolution of the field, highlighting the introduction of revolutionary new technologies and social media platforms. With a heavy focus on emerging industry trends and the positive impacts of technology on HR, the 17th Edition prepares you with everything you need to be effective managers and HR personnel in the 21st century.